Evaluating clinical and demographic influences on health perception: A translation of the SF-12 for use with NHANES. (June 2022) - Covert, Elise C.; Baker, Anna M.; Gilani, Owais
Abstract: Improving public health depends on an intricate understanding of the factors that influence how individuals perceive and self-report their personal health. Self-perceived health is an independent predictor of future health-related outcomes, but capturing self-perception of health is complex due to the intricate relationship between clinical and perceived health. A commonly used measure of self-perceived health is the Short Form 12 (SF-12), developed in the 1990s. In this study, we aim to evaluate clinical and demographic influences on self-perceived health among American adults using the National Health and Nutrition Examination Survey (NHANES). While NHANES captures information on a number of domains of health, including clinical assessments, it does not include SF-12 items necessary to measure self-perceived health. Therefore, to assess self-perceived health for our study, we constructed and validated a novel SF-12-equivalent measure for use with NHANES using analogous items from the 2015–2016 NHANES interview questionnaires. The developed measure reflects established knowledge of population health patterns and closely parallels the behavior of the original SF-12. An analysis of the clinical and demographic influences on this novel measure of health perception revealed that both clinical and demographic factors, such as depression status and race, influence how healthy individuals perceive themselves to be. Importantly, our analysis indicated that among American adults, while controlling for clinical and demographic covariates, an increase in low-density lipoprotein (i.e., "bad") cholesterol level was associated with an improvement in self-perceived health. This study contributes significantly in two domains: it provides a novel measure of self-perceived health compatible for use with the widely used NHANES data (as well as details on how the process was developed), and it identifies a critical area in need of improved clinical education regarding the apparent confusion around cholesterol health. Highlights: Both clinical and demographic factors significantly influence health perception. Increased "bad" cholesterol paradoxically associated with better perceived health. Novel perceived health measure is reproducible with publicly available survey data. Understanding health perception patterns can inform health education and promotion.